A Production and operations management study on Honda Philippines, Inc. - Balagtas, Paula; Butac, Alec.; Custodio, Margarett; Vargas, Vina. (Diliman, Quezon City College of Engineering, 2003)
The purpose of this study conducted on Honda Philippines Inc. is to discover possible means of improving operations processes performed by the company. BY documenting the current operations management methods, specifically strategic issues concerning: design, quality, process design, location selection, layout design, human resources and job design, supply chain management, inventory, scheduling, and maintenance, the paper will try then to find any improvements to better the company's operations through the use of Industrial Engineering Tools. Improvements were then suggested as follows: In forecasting, exponential smoothing with trend adjustments could be a way of lessening holding and stockout costs; In capacity planning, the a fuel tank should be installed in place of the body frame welding line to possible increase profit; In aggregate planning an alternative of increasing the rate of production of 6500 units of motorcycles per month can be a way of decreasing costs.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Honda Philippines Incorporated; Automobile industry; Production engineering